Prioritizing of bacterial infections transmitted through substances of human origin in Europe. Issue 5 (24th February 2017) - Domanović, Dragoslav; Cassini, Alessandro; Bekeredjian‐Ding, Isabelle; Bokhorst, Arlinke; Bouwknegt, Martijn; Facco, Giuseppina; Galea, George; Grossi, Paolo; Jashari, Ramadan; Jungbauer, Christoph; Marcelis, Jan; Raluca‐Siska, Ioana; et al.
Abstract : BACKGROUND: Bacteria are the pathogens most frequently transmitted through substances of human origin (SoHO). The European Centre for Disease Prevention and Control (ECDC) organized an expert consultation, with the objective of developing a priority list of bacterial pathogens transmissible via SoHO. The list will be used to further assess risks and determine appropriate preventive measures. STUDY DESIGN AND METHODS: The 14 most frequently SoHO‐transmitted bacteria identified through a scoping literature review were then prioritized during an expert workshop through a methodology based on multicriteria decision analysis. The selection of the prioritization method was based upon an ECDC framework for best practices in conducting risk‐ranking exercises. Three transmission pathways, blood and blood components, tissues and cells, and organs, were considered in the ranking exercise. RESULTS: According to the ranking score (RS), bacteria were organized within each SoHO pathway into one of four risk tiers: Tier 1 (RS ≥ 0.70), Tier 2 (RS = 0.60‐0.69), Tier 3 (RS = 0.40‐0.59), or Tier 4 (RS < 0.40). The most consistently identified pathogens in the highest risk Tiers 1 and 2 of all three pathways were: Staphylococcus aureus, Klebsiella spp., Escherichia coli, β‐hemolytic streptococci, Pseudomonas spp., and Acinetobacter spp. CONCLUSION: Six bacteria were defined as being of the highest priority in respect of the threat to the safety of SoHO and will be the subject of subsequent in‐depth risk assessments to be conducted by ECDC to identify measures to mitigate the risk posed by these bacteria.